Maternal diabetes impairs oxidative and inflammatory response in murine placenta - Saad, Mohamed I. (Springerplus, 2016)
Placenta is the major exchange surface between mother and fetus and plays a pivotal role in fetal development. A better understanding of the mechanisms by which diabetes alters placental function may allow better management of diabetes pregnancies. In this study, we attempt to investigate the effect of diabetic milieu with and without malformation on placental function. In order to investigate the impact of diabetic pregnancy on oxidative stress, endothelial and vascular functions of placental tissue, we mated diabetic and non-diabetic female rats with normal male rats. At gestational day 17, we terminated pregnancy, assessed fetuses for malformations and isolated placenta for measurement of various parameters of placental function. Our results show that maternal diabetes induced a state of oxidative stress in placenta, which disrupts normal signaling, activating apoptosis, as well as perturbing endothelial and vascular placental functions. The coalescence of these insults on various levels of placental function could contribute to the pleiotropic nature of diabetes-induced placental stress.